PENDAMPINGAN RAPAT ANGGOTA TAHUNAN KSP KOPDIT OBOR MAS - Yosefina Andia Dekrita; Konstantinus Pati Sanga; Stefania Evarista Nona Cici (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Annual Members’ Meeting (Rapat Anggota Tahunan or RAT) is the highest forum in cooperatives, serving as a medium for the board’s accountability to members as well as a venue for strategic decision-making. KSP Kopdit Obor Mas, one of the largest cooperatives in Eastern Indonesia with more than 240,000 members and assets reaching IDR 7.8 trillion, faces several challenges in conducting RAT, including low member participation, the complexity of financial reports, and the demand for compliance with regulations and the cooperative’s Articles of Association/Bylaws. This community service activity aimed to assist the implementation of RAT to ensure greater transparency, participation, and accountability. The methods included coordination with the board and supervisory committee, preparation of mentoring modules, socialization, simplification of financial reports, RAT simulations, and forum evaluation. The results show increased member participation, more accessible financial reporting, and a better-organized RAT conducted in accordance with regulations. The discussion highlights that mentoring activities strengthen Good Cooperative Governance and improve cooperative management practices. Thus, this activity contributes to enhancing institutional capacity and can serve as a model for sustainable cooperative development in other regions.